2005
DOI: 10.1161/01.res.0000181286.44222.61
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine and the Risk of Cardiovascular Events and Death in Patients With Coronary Artery Disease

Abstract: Abstract-As a competitive inhibitor of endothelial nitric oxide synthase, asymmetric dimethylarginine (ADMA) has been related to atherosclerotic disease. Little is known about the prognostic impact of baseline ADMA determination. Key Words: asymmetric dimethylarginine Ⅲ cardiovascular risk Ⅲ coronary artery disease T he endothelium plays a crucial role in the regulation of vascular tone. 1 A factor of prime importance to maintain endothelial homeostasis is nitric oxide. 2 Apart from its vasodilating effects, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
218
6
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(249 citation statements)
references
References 56 publications
16
218
6
9
Order By: Relevance
“…Unlike the majority of previous studies such as [58,59], we did not see significantly higher baseline CRP levels among smokers within this study; although a current meta-analysis should confirm the relationship between smoking status and CRP [60], as results have not always been consistent [61]. However, we did show that smokers had significantly higher baseline ADMA levels than non-smokers within this population, which has been previously reported in some [62][63][64], although not all [65,66] studies. When the analysis (percentage of baseline ADMA and CRP at 8 weeks) was stratified by smoking status, we observed no statistically significant differences between the four groups in response to supplementation.…”
Section: Discussioncontrasting
confidence: 89%
“…Unlike the majority of previous studies such as [58,59], we did not see significantly higher baseline CRP levels among smokers within this study; although a current meta-analysis should confirm the relationship between smoking status and CRP [60], as results have not always been consistent [61]. However, we did show that smokers had significantly higher baseline ADMA levels than non-smokers within this population, which has been previously reported in some [62][63][64], although not all [65,66] studies. When the analysis (percentage of baseline ADMA and CRP at 8 weeks) was stratified by smoking status, we observed no statistically significant differences between the four groups in response to supplementation.…”
Section: Discussioncontrasting
confidence: 89%
“…With regard to the composite outcomes, the estimated study power in this study was 0.71. Although the mortality rate was relatively low in our high-risk population, in comparison with other similar studies (15,21), the eGFR of our population with CKD was relatively higher, which might be associated with the better outcome of our high-risk cohort. In addition, antiplatelet agents (86.9%) and statins (60.4%) were administered commonly in our patients, which might be another contributing factor to the better outcome in our patients.…”
Section: Discussioncontrasting
confidence: 70%
“…Several studies have shown that plasma ADMA level may predict the progression of renal injury in patients with early-stage CKD (12,13). In addition, high plasma ADMA level has been reported to be an independent risk factor for cardiovascular disease and allcause mortality in a community-based population (14), in patients with coronary artery disease (CAD) (15,16), and in patients with ESRD (17,18). However, evidence about the association between ADMA and patients with mild to moderate CKD is limited.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Studies have demonstrated a significant association between elevated ADMA levels and cardiovascular disease. 10,11 Infusion of ADMA is associated with endothelial dysfunction. 12 The ratio of L-arginine to ADMA is associated with altered NOS activity 13 and is a useful index for evaluating the effects of ADMA.…”
Section: Introductionmentioning
confidence: 99%